Dating Kitab Tibb MSS 3290: Watermark analysis and orthographic evolution in Malay medical manuscripts - Mohd 'Azmi Mohd Razif (Universiti Sains Islam Malaysia, 2025)
Ulum Islamiyyah, Volume 37 Issue 03 Page (19–34)